Pendekatan Polifasik Pada Eksplorasi Bakteri Asam Laktat dari Tempoyak di Sumatera Selatan - Soleha, Siti; Atina Qurba Hanifa (Universitas Pendidikan Ganesha, 2024)
The polyphasic approach is a comprehensive method for classifying bacterial isolates into specific. It combines morphological and biochemical data with molecular details, such as 16S rRNA gene sequencing. This study aims to identify LAB (Lactic Acid Bacteria) species found in tempoyak from South Sumatra. The identification process includes examining colony morphology, cell morphology, physiology biochemistry, and analyzing the 16S rRNA gene of LAB. The physiological and biochemical characteristics of LAB were observed through test such as oxygen requirement, motility, indole, catalase, MR-VP, citrate, urea, and sugar fermentation. The Morphological, biochemical and physiological characteristics were compared to those in Bergey's Manual of Determinative Bacteriology. The 16S rRNA gene was amplified using universal primers 27F (5' AGA GTT TGA TCM TGG CTC AG 3') and 1492R (5' TAC GGY TAC CTT GTT ACG ACT T 3'). DNA sequences in FASTA format were compared to NCBI DNA database using BLAST software. A Phylogenetic tree was reconstructed using the Maximum likelihood method in MEGA X with a bootstrap of 1000. This study successfully isolated three LAB, coded as TP02, TP07 and TP08. TP02 was identified as Lactobacillus sp, YIT 11469, TP07 as Lentilactobacilus kefiri strain NBRC 15888 and TP08 as Lentilactobacillus buchneri strain JCM 1115. TP02 and TP08 showed strain level similarity with identity percentages of 99.93% and 99.60%, respectively.